An overview of free radical research - Matkovics, András (Acta Biologica Szegediensis, 2003)
The discovery of the pathogenetic role of free radicals in various human and animal diseases initiated a wide range of investigations, resulting in a number of important scientific dicoveries. These are reviewed in this paper, with an emphasis on preventing atherosclerotic complications and plaque development. The administration of antioxidants in the prevention and therapy of different diseases is listed, too. The questions of optimum antioxidant supply to prevent atherosclerosis, malignancies and other diseases are discussed.